Endostatin induces normalization of blood vessels in colorectal cancer and promotes infiltration of CD8+ T cells to improve anti-PD-L1 immunotherapy - Chu, Xiao-Dong; Bao, Hui; Lin, Yu-Jian; Chen, Ruo-Xi; Zhang, Yi-Ran; Huang, Ting; He, Jia-Shuai; Huangfu, Shu-Chen; Pan, Yun-Long; Ding, Hui (Frontiers in Immunology, 2022)
Abstract Introduction: The purpose of this study was to evaluate recombinant human endostatin (rHEs)-induced normalization of the tumor vasculature in colorectal cancer (CRC) and to evaluate the therapeutic effects of combined treatment with rHEs and programmed death ligand-1(PD-L1) inhibitors. Methods: A mouse subcutaneous tumorigenesis model was established to evaluate the antitumor effects of endostatin combined with a PD-L1 inhibitor on CRC. Intravoxel incoherent motion diffusion-weighted magnetic resonance imaging (IVIM-DW MRI) was used to evaluate changes in the intra-tumor microcirculation in response to combined treatment with endostatin and a PD-L1 inhibitor. The infiltration density and function of CD8+T cells in tumors was evaluated using flow cytometry. Finally, clinical specimens were used to evaluate the expression area of tumor vascular pericytes and CD8+ T cells in tumor tissues. Results: The antitumor effects of endostatin combined with PD-L1 inhibitor were significantly greater than those of endostatin or PD-L1 inhibitor alone. On the ninth day of intervention, the endostatin group showed significantly higher D* and F values in tumors than those in the control group or PD-L1 group. After 27 days of intervention, the endostatin groups showed significantly lower levels of VEGF and TGF-β than the control group. Treatment of CD8+ T cells with endostatin for 24 hours did not alter the expression levels of markers of reduced T cell activity. However, endostatin reversed VEGF-mediated inhibition of secretion of IFN-γ from T cells. The results in colorectal cancer clinical samples showed that treatment with endostatin induced significantly higher infiltration of CD8+T cells compared with treatment that did not include endostatin. Furthermore, the expression area of pericytes was significantly positively related to infiltration density of CD8+T cells and overall survival time. Conclusion: Endostatin improved the anti-tumor effects of PD-L1 inhibitors on colorectal cancer, significantly increased the activity of CD8+ T cells, and synergistically improve the tumor treatment effect of the two inhibitors.